Organization capital and firm life cycle - Hasan, Mostafa; Cheung, A. (Elsevier BV * North-Holland, 2018)
We hypothesize, and examine empirically, two types of association between organization capital and firm life cycle. Are firms with high organization capital more likely to be in a particular stage of their life cycle than firms with low organization capital? Are firms' transitions from one life cycle stage to another over time associated with how much they invest in organization capital? Our findings suggest that firms with high (low) organization capital are more likely to be in the introduction and decline (growth and maturity) stages. Our results also show that firms that invest more in organization capital (i.e., changes in organization capital) are less (more) likely to move to the introduction, shake-out and decline (growth and maturity) stages in the subsequent five years. Our results are robust to alternative specifications of organization capital, life cycle proxies and endogeneity concerns.